PENINGKATAN NILAI CBR TANAH LEMPUNG DENGAN MENGGUNAKAN SEMEN UNTUK TIMBUNAN JALA - Apriyanti, Yayuk (SIPIL, 2013)
The subgrade used for a highway construction should have a good bearing capacity, because the loads applied on the road construction are static and dynamic loads. One parameter that we can use to determine whether the soil bearing capacity is good or poor is by knowing the CBR value. The better the bearing capacity is, the higher the CBR. A poor bearing subgrade can be replaced with better soil (hoard with soil) from other location. Often there is no option for the hoarding material, so soil with high plasticity like A7 is used. To solve this problem, one of the efforts taken to enhance the soil bearing capacity is soil remediation using chemical stabilization method with cement. The percentage variations of the cement used are 10%, 12,5% and 15% with curing age of 1,7,14, and 28 days, optimum water condition. The tests that are conducted includes physical and mechanical properties tests of the original soil and mechanical properties testing of the stabilized one (soil CBR). From the result it is known that the CBR value rises with the percentage of cement (compared to the original soil CBR). The maximum CBR in 15% cement is 69,31%. The CBR value of the undisturbed soil is 3,01%. The CBR also increases with the age of curing from 1 to 28 days.Key Words: Hoarding material, Cement, Stabilization, Optimum, CBR.